Butterfly Gardening in Florida - Jaret C. Daniels; Joe Schaefer; Craig N. Huegel; Frank J. Mazzotti (EDIS)
Revised! WEC-22, a 25-page fact sheet by Jaret C. Daniels, Joe Schaefer, Craig N. Huegel, and Frank J. Mazzotti, includes how to plan for a butterfly garden, butterfly facts and biology, resources needed for adult butterfly and larvae (caterpillars), a map of butterfly regions and extensive tables. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, February 2008.